(untitled) (Khairulummah, 2023)
Arabic rhetoric and its uses of various styles for religious purposes: the styles of exposure ((التعريض as an example in the holy Quran. The Quranic expressing and its study cannot be understated for the correct understanding of the religion of Islam except this terms. Some scholars of Islam have even gone as far as to label the studying of the Arabic language as wajib – or even fardh. Furthermore, the understanding of the style of the Qur’anic elucidation and the subtleties of the treasures of Qur’anic knowledge too are dependent upon knowledge of the different fields of the Arabic language, so much so that it would be completely appropriate to say that they are to a large extent interconnected. Since the beginning the study of Arabic language has been held in high esteem from both Muslims and non-Muslims alike – its study uniting both groups from various tribes and lands with common respect. This was never just restricted to language, rather it encompassed an entire culture. In this research paper, I have discussed the majestic beauty of the use of various styles of exposure ((التعريض and its purposes with examples from various Ayahs of the holy Qur’an where mentioned expounded upon how the knowledge of rhetoric is helps in understanding in the Qur’an expressing . exposure